Organizational learning: Cognitive and behavioural changes and implications in higher education institutions - Alexandra Luciana Guță (CES Working Papers, 2018)
Many facets of the concept of “organizational learning” and many ideas about it have been debated in the literature. One of the issues raised is whether organizational learning necessarily needs to encompass changes at both cognitive and behavioural levels in an organization or if one of these two types of changes is enough. The issue is even more complicated because changes in behaviour could be also related to adaptation and not learning. There is also the question if learning has really occurred if there is no change in behaviour, but only in cognition. Also, are organizational learning and changes in cognition or behaviour always beneficial for an organization? Therefore, the paper explores and expresses our position in the matter of the cognitive and behavioural dilemma regarding organizational learning. We are approaching these issues, as well as presenting some implications in the case of higher education institutions.
Keywords: D83; 330; organizational learning; cognitive/ behavioural changes; higher education institutions